'Alive after five': Constructing the neoliberal night in Newcastle upon Tyne. (February 2015) - Shaw, Robert
The development of the 'night-time economy' in the UK through the 1990s has been associated with neoliberal urban governance. Academics have, however, begun to question the use and the scope of the concept of 'neoliberalism'. This paper identifies two common approaches to studying neoliberalism, one exploring neoliberalism as a series of policy networks, the other exploring neoliberalism as the governance of subjectivities. It is argued that to understand the urban night, we need to explore both these senses of 'neoliberalism'. As a case study, the paper takes the 'Alive After Five' project, organised by the Business Improvement District in Newcastle upon Tyne, which sought to extend shopping hours in order to encourage more people to use the city at night. Drawing from actor–network theory, the planning, the translation and the practice of this new project are explored together with the on-going nature and influence of neoliberal policy on the urban night in the UK.